Snow Samples Combined With Long-Range Transport Modeling to Reveal the Origin and Temporal Variability of Black Carbon in Seasonal Snow in Sodankylä (67°N) - Meinander, Outi; Kontu, Anna; Kouznetsov, Rostislav; Sofiev, Mikhail (Frontiers in Earth Science, 2020)
In the Arctic areas, the influence of global climate change is enhanced. Enabling a better understanding of the changes in the Arctic environment is of the utmost importance. The deposition of local and long-range transported air pollutants includes light-absorbing aerosols, such as black carbon (BC), which darken bright surfaces and induce snow melt. In 2009–2013, surface snow was sampled on a weekly basis during autumn, winter and spring at the Arctic Space Centre of the Finnish Meteorological Institute in Sodankylä, which is located north of the Arctic Circle (67.37o N, 26.63o E). Snow samples were analyzed for BC with an Organic/Elemental Carbon Aerosol (OCEC) analyzer. These data were combined with SILAM modeling (System for Integrated modeLing of Atmospheric coMposition) to reveal the origin and temporal variability of BC in seasonal snow. Quantitative footprint calculations for the BC observations were performed with the SILAM -model considering emission sources at all heights and including also the sensitivity to the local and near-surface sources. The median BC concentration in snow was 25 µg/kg (n = 107, skewness γ1 = 0.12, 75th percentile Q3 = 42 µg/kg), determined as [μg-EC/L-H2O]. During snow accumulation season, the median surface snow BC concentration was 21µg/kg (n = 78, γ1 = 1.5, Q3 = 33 µg/kg), and during melt season, it was 57 µg/kg (n = 29, γ1 = 2.2, Q3 = 85 µg/kg). The melt period was identified using snow depth data from the Sodankylä station. The highest BC values in spring represented the enrichment of BC to the snow surface due to seasonal snow melt. The spring melt BC enrichment ratio was 2.7 (calculated as the ratio of median melt season concentration to median accumulation season snow concentration). The results showed that increased surface snow BC concentrations (> 30 µg/kg) were due to air masses originating from the Murmansk region in Russia, where smelting and mining industries are located. The temporal variability of BC in snow was high and depended on atmospheric and cryospheric processes, mostly the origin of BC due to atmospheric transport and dry and wet deposition processes, as well as post-depositional snow processes.